A espera do lado de fora: uma análise da espera pelas visitas em Itirapina - SP - Demari, Nayara Veiga (Universidade Federal de São Carlos, 2022)
This work seeks to analyze the waiting processes that go through visits to the São Paulo penitentiary system in the moments before passing through the entrance gate of the penal units. Through a bibliographical review and observations made during the production of the documentary "From grade to here", the waiting processes that are imposed on visits are observed, which manage waits in order to limit them as much as possible. Despite this effort, these wait management processes can be interrupted when an unsuspecting transfer occurs and visitors need to reorganize themselves to visit again, leaving behind all the effort mobilized to carry out the visit.
Waiting outside: an analysis of waiting for prison visitors in Itirapina - SP
Keywords: Familiares; Visitas; Prisões; Espera; CIENCIAS HUMANAS::SOCIOLOGIA